The analysis of methylation of DNA promoter of SFRP2 gene in patients with hyperplastic processes of the endometrium - Marichereda, V.G.; Bykovа, N.A.; Bubnov, V.V.; Manasova, G.S.; Moskalenko, T.Y.; Volyanska, A.G.; Shevchenko, I.M.; Adamovska, T.M. (Experimental Oncology, 2018)
The hyperplastic processes of the endometrium can arise not only against the background of excessive influence of estrogen, but also against the background of epigenetic damages that affect apoptosis, cell proliferation, differentiation, and adhesion, and DNA reparation. The aim of our study was to investigate and analyze the status of methylation of the promoter of SFRP2 gene in patients with hyperplastic processes of the endometrium. Materials and Methods: The study groups were the following: I — patients with endometrial hyperplasia (EH, n = 9); II — patients with endometrial intraepithelial neoplasia (EIN, n = 10), III — control groups: 1) with endometrial cancer (EC, n = 4), and 2) healthy women (n = 4). Determination of promoter methylation of SFRP2 gene was carried out by the semiquantitative method of methylation-specific PCR assay. Results: The maximum level of methylation of SFRP2 gene promoter had been revealed in patients with EC — 42.80 ± 3.55% (р < 0.05). The patients of the I group had the lowest values of methylation of SFRP2 gene promoter — 10.66 ± 0.85%, while in patients of the II group this indicator was higher — 20.60 ± 0.95% (р < 0.05). In healthy women of the control group, methylation of SFRP2 gene promoter was detected in none of the samples. Conclusion: The content of the methylated SFRP2 gene in endometrial tissue of patients with hyperplastic processes higher than 20–25% allows relate these women to the risk group of EC development and dictates the need of intensive observation of such patients. Key Words: methylation, SFRP2 gene, hyperplastic processes of the endometrium.